2021
DOI: 10.5946/ce.2020.068
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Comparison of the AIMS65 Score, Glasgow-Blatchford Score, and Rockall Score for Predicting Clinical Outcomes in Patients with Variceal and Nonvariceal Upper Gastrointestinal Bleeding

Abstract: Upper gastrointestinal bleeding (UGIB) is a common cause of hospital admission worldwide, and has a mortality rate of between 2% and 15%. 1 Recent guidelines have recommended stratifying patients with UGIB into higher and lower risk categories for treatment decisions and prognostication. 1-3 The widely used scoring systems include the Glasgow-Blatchford score (GBS), Rockall score (RS), and AIMS65 score (AIMS65) (Table 1); however, their role in clinical practice remains uncertain. 4-6 Compared with other exist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 31 publications
(56 reference statements)
4
21
0
Order By: Relevance
“…23 Risk scores help predict occurrences of mortality during the hospital stay, the frequency of rebleeding, the need for transfusion and the need for hemostatic procedures through endoscopy. [1][2][3]24 In a study comparing the RS with other risk scores, the AUC value (AUC: 0.624; P < 0.05) for the RS of patients who needed transfusion was similar to that of our study (AUC: 0.648; P = 0.002). 24 In the same study, when the cutoff value for the RS was taken as 6, the sensitivity was 42.9% and the specificity was 90.5%, for predicting mortality.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…23 Risk scores help predict occurrences of mortality during the hospital stay, the frequency of rebleeding, the need for transfusion and the need for hemostatic procedures through endoscopy. [1][2][3]24 In a study comparing the RS with other risk scores, the AUC value (AUC: 0.624; P < 0.05) for the RS of patients who needed transfusion was similar to that of our study (AUC: 0.648; P = 0.002). 24 In the same study, when the cutoff value for the RS was taken as 6, the sensitivity was 42.9% and the specificity was 90.5%, for predicting mortality.…”
Section: Discussionsupporting
confidence: 83%
“…[1][2][3]24 In a study comparing the RS with other risk scores, the AUC value (AUC: 0.624; P < 0.05) for the RS of patients who needed transfusion was similar to that of our study (AUC: 0.648; P = 0.002). 24 In the same study, when the cutoff value for the RS was taken as 6, the sensitivity was 42.9% and the specificity was 90.5%, for predicting mortality. 24 In our study, in terms of predicting mortality, the sensitivity was calculated as 70.6% and the specificity was 62.2% when the cutoff value for RS was taken as 7; while the sensitivity was 57.8% and the specificity was 85.3% when the cutoff value for PI was taken as 1.1.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…On the contrary, our study population is different geographically and chronologically, and represents a true external validation. In a recent external validation study, Chang et al reported an AUROC of 0.8 for GBS, which is similar to the value we found in our study [12]. In another study, Chan and al.…”
Section: Comparison With Other Publicationssupporting
confidence: 92%
“…The data collected included age, sex, hypertension, diabetes, cerebral vascular disease, cardiovascular disease, chronic lung disease (chronic obstructive pulmonary disease, asthma, interstitial lung disease), chronic liver disease, chronic kidney disease, reason for ICU admission, Simplified Acute Physiology Score (SAPS) II at ICU admission, and length of ICU stay before suspected GI bleeding. Information on the PaO 2 /FiO 2 ratio (PF ratio), Glasgow-Blatchford score (GBS), [ 10 ] initiation of mechanical ventilation, vasopressor use, EGD findings, and laboratory findings on suspected GI bleeding were also retrieved. The outcomes were: requirement of red blood cell (RBC) transfusion and change of hemoglobin level for a week after suspected GI bleeding, re-suspected bleeding events requiring RBC transfusion during hospital stay (from 1 week after suspected GI bleeding to last hospital day), length of ICU stay, and ICU mortality.…”
Section: Methodsmentioning
confidence: 99%